Oxidation behaviour of 8.6 Al-Cu alloy in South China Seawater - Mohammed Misbahul, Amin; Seoh Soo Yee; W. B., Wan Nik (Sadguru Publications, 2009)
The corrosion behavior of 8.6 Al-Cu alloy was investigated in 4 different conditions of South China Seawater. The weight loss curve of alloy increases with time during the initial exposure period, due to dissolution of deposit. The films formed were thick, porous and adhered on the surface of the alloy. The seawater species have deleterious effect on the protectively of the surface and rapid degradation of the alloy is noted. The morphologies of deposits on the surface of alloy were determined by using polarized microscope.